Motives of Transcarpathian architecture in Zoltan Sholtes creativity - Мельник, Оксана; Штець, Віктор (Київський національний університет імені Тараса Шевченка, 2022)
The article reveals the peculiarities of Zoltan Sholtes' work in the open air. The typological characteristics of the artist's landscapes by thematic and semantic aspects are determined. Landscape with architectural motifs is one of the dominant plots, along with a lyrical chamber sketch, a rural landscape and a panoramic landscape-picture. Some landscapes with motifs of Transcarpathian architecture, in addition to artistic value, have ethnographic value, as they show architectural monuments that have not been preserved to this day. Art analysis of landscapes with motifs of the fortifications of Uzhgorod and Mukachevo, as well as wooden bell towers and churches showed the peculiarities of the creative method. This is work in the open air, solving pictorial and figurative tasks, the use of realistic-impressionist means of artistic expression. The plein air experience contributed to the formation of a recognizable author's handwriting of the artist. This is a special approach to the interpretation of planning and spatial relationships; compositional division of the canvas into plans with a high horizon line and a blank foreground; use of vibrating expressive writing technique a la Prima; combination of active modeling smear with transparent generalized planes; color experiments, a special ratio of warm and cold shades in particular. The main means of emotional expression of the works are defined by color means; means of author's equipment; composite means; figurative means, expressed through the peculiarities of the interpretation of the planes of the foreground and the sky, which enhance the emotional component of the landscape. Detailed reproduction of a visible plot with an architectural object and the search for a unique image inspired by this plot, the formation of the appropriate mood, and the manifestation of philosophical, symbolic subtext determine the peculiarity of the artist's creative method.

У статті розкрито особливості роботи Золтана Шолтеса на пленері та виявлено типологічні характеристики пейзажів мистця за тематично-змістовими аспектами. Поряд з ліричним камерним етюдом, сільським пейзажем та панорамним пейзажем-картиною виділено пейзаж з архітектурними мотивами як один з домінуючих напрямів творчого пошуку художника. Окремі пейзажі з мотивами закарпатського зодчества, окрім художньої мають етнографічну цінність, позаяк фіксують пам’ятки, не збережені до наших днів. Мистецтвознавчий аналіз пейзажів з мотивами оборонних споруд Ужгорода та Мукачева, а також дерев’яних дзвіниць та церков показав, що творчий метод мистця передбачає роботу на пленері з вирішенням живописних та образних завдань та використанням реалістично-імпресіоністичних засобів художньої виразності. Пленерний досвід сприяв формуванню упізнаваного авторського почерку художника –  особливого підходу до трактування плановості та просторових співвідношень; композиційного членування полотна з високою лінією горизонту та порожнім першим планом; використання вібруючої експресивної техніки письма а-ля-прима; поєднання активного моделюючого мазка з прозорими узагальненими площинами; колористичних експериментів, зокрема, особливого співвідношення теплих та холодних відтінків. Основними засобами емоційної виразності творів визначено колористичні засоби; засоби авторської техніки; композиційні засоби; образні засоби, виражені через особливості трактування великих площин переднього плану та неба, що посилюють емоційну складову пейзажу. Особливістю творчого методу художника визначено не просто детальне відтворення видимого сюжету з архітектурним об’єктом, а пошук навіяного цим сюжетом унікального образу, формування відповідного настрою, вияв філософського, символічного підтексту.
Архітектурні мотиви Закарпаття у творчості Золтана Шолтеса
Keywords: Z. Sholtes; Transcarpathian school of painting; landscape; architectural motives; means of expression; creative method; З.Шолтес; Закарпатська школа живопису; пейзаж; архітектурні мотиви; засоби виразності; творчий метод